2011
DOI: 10.1016/j.isprsjprs.2011.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of chromophoric dissolved organic matter in Mandovi and Zuari estuaries — A study through in situ and satellite data

Abstract: The spatial and temporal distribution of absorption of chromophoric dissolved organic matter at 440 nm (a CDOM (440)) in Mandovi and Zuari estuaries situated along the west coast of India, has been analyzed. The study was carried out using remotely sensed data, obtained from the Ocean Colour Monitor (OCM) on board the Indian Remote Sensing satellite -P4, together with in situ data during the period January to December 2005. Satellite retrieval of CDOM absorption was carried out by applying an algorithm develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Nevertheless, the most robust relationship (R ¼ À0.94) was found during cold months suggesting the influence of the adjacent inner shelf waters (Carvalho et al, 2014). A contribution to CDOM by sediment resuspension (e.g., Menon et al, 2011) was ruled out, as no correlation was found between TSM and a cdom (443). Local CDOM produced by the degradation of algal estuarine species, and bacteria consumption will likely modify the characteristics of CDOM.…”
Section: Time Variability Of Optical Parametersmentioning
confidence: 99%
“…Nevertheless, the most robust relationship (R ¼ À0.94) was found during cold months suggesting the influence of the adjacent inner shelf waters (Carvalho et al, 2014). A contribution to CDOM by sediment resuspension (e.g., Menon et al, 2011) was ruled out, as no correlation was found between TSM and a cdom (443). Local CDOM produced by the degradation of algal estuarine species, and bacteria consumption will likely modify the characteristics of CDOM.…”
Section: Time Variability Of Optical Parametersmentioning
confidence: 99%
“…A decrease in salinity of coastal surface waters is known to occur during the SW monsoon due to freshwater supply through the short but numerous rivers along the Indian west coast (Jayakumar et al, 2001;Suprit and Shankar, 2008). Based on the analysis of satellite data, Menon et al (2011) showed the presence of chromophoric terrestrially-derived dissolved organic matter (CDOM) in the Mandovi estuary in response to increased river runoff during the monsoon season. These findings illustrate that during the monsoon season river-derived organic material does reach offshore areas where it might be dispersed with the coastal current.…”
Section: Sw Monsoonmentioning
confidence: 99%
“…During the southwest monsoon season a strong negative correlation (R = -0.6) was observed between a CDOM 440 and salinity, but in other months no significant correlation was found. River discharge is the major contributor of CDOM in coastal waters, but resuspension and in situ degradation can also enhance CDOM (Menon et al 2011). Similarly, the potential source of TSM is either from rivers or due to resuspension in shallow waters.…”
Section: Discussionmentioning
confidence: 99%